A study of microalgae cultivation in hydrothermal carbonization process water: Nutrient recycling, characterization and process design - Kocer, Anil Tevfik; Inan, Benan; Ozcimen, Didem; Gokalp, Iskender (ELSEVIER, 2023)
The disposal or recycling of the hydrothermal carbonization (HTC) process water is crucial in environmental and economical aspects due to having short-chain organic acids and ammonia and compounds that show toxic effects even at low concentrations. The aim of this study is to utilize the process water in different concentrations (0.25%- 2%) which released from HTC of orange and olive pomace for Chlorella sorokiniana production. In this study, the optimum growth rate and doubling time were calculated as 0.16 +/- 0.02 day-1 and 4.44 +/- 0.82 days, respectively. Also, it was observed that the type and concentration of the process water did not change the biochemical content of microalgae significantly. It was seen that the carbohydrate, lipid and protein contents of microalgae changed between 32.25 +/- 2.66% - 35.03 +/- 1.51%, 12.71 +/- 3.94% 14.33 +/- 2.36 and 35.36 +/- 3.92% - 41.22 +/- 1.72%, respectively. Moreover, for the first time, presentation of a process design and simulation of microalgae production using HTC process water was performed. As a result of the experiments and assessments, it was determined that HTC aqueous phase can be used for the cultivation of C. sorokiniana. In this way, microalgae biomass, which is a value-added product, will be produced and the toxic substances in HTC process water will be utilized.(c) 2023 The Author(s). Published by Elsevier B.V. This is an open access article under the CC BY-NC-ND license (http://creativecommons.org/licenses/by-nc-nd/4.0/).
Keywords: Nutrient recovery; HTC process water; Microalgae cultivation; Chlorella sorokiniana; Process design; CHLORELLA-SOROKINIANA; AQUEOUS-PHASE; LIPID PRODUCTION; LIQUEFACTION; BIOMASS; STRAINS; CULTURE; GROWTH; Biotechnology & Applied Microbiology; Engineering; Environmental Sciences & Ecology